2009
DOI: 10.1037/a0015155
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in structured risk assessment: Comparing the accuracy of five instruments.

Abstract: Structured risk assessment should guide clinical risk management, but it is uncertain which instrument has the highest predictive accuracy among men and women. In the present study, the authors compared the Psychopathy Checklist-Revised (PCL-R; R. D. Hare, 1991, 2003); the Historical, Clinical, Risk Management-20 (HCR-20; C. D. Webster, K. S. Douglas, D. Eaves, & S. D. Hart, 1997); the Risk Matrix 2000-Violence (RM2000[V]; D. Thornton et al., 2003); the Violence Risk Appraisal Guide (VRAG; V. L. Quinsey, G. T.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
95
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(108 citation statements)
references
References 61 publications
11
95
0
2
Order By: Relevance
“…None of the LSI instruments were evaluated with psychiatric samples. The PCL-R was able to predict recidivism with moderate accuracy in a correctional sample (AUC = .73; Coid et al, 2009), but the same was not found for a psychiatric sample (AUC = .57; Schaap et al, 2009). When the primary author compared effect sizes between the correctional and psychiatric sample using independent t-tests, no significant differences were found (p N .05).…”
Section: N = 15mentioning
confidence: 46%
See 2 more Smart Citations
“…None of the LSI instruments were evaluated with psychiatric samples. The PCL-R was able to predict recidivism with moderate accuracy in a correctional sample (AUC = .73; Coid et al, 2009), but the same was not found for a psychiatric sample (AUC = .57; Schaap et al, 2009). When the primary author compared effect sizes between the correctional and psychiatric sample using independent t-tests, no significant differences were found (p N .05).…”
Section: N = 15mentioning
confidence: 46%
“…Duplicates identified n = 62 (AUC = .70) in one correctional sample (Coid et al, 2009), but not in another (Warren et al, 2005). However, the 95% confidence interval for the AUC in Coid et al's (2009) study was wide suggesting that obtained AUC values cannot be interpreted with confidence.…”
Section: N = 15mentioning
confidence: 63%
See 1 more Smart Citation
“…Step 2 covariates age and gender added best performing scales was evident at the median split; 65% for the HCR-20 and 66% for the NAS, and the relative predictive accuracy of the all the risk measures is moderate when compared with the larger effects found in other similar studies in forensic, mixed, prison and learning disability samples [4,8,9]. For the purposes of this study the sample comprised of discharged acute psychiatric patients.…”
Section: Measurementioning
confidence: 99%
“…Coid et al [7,8] investigated risk factors and five structured risk assessment instruments associated with offending post-discharge from medium secure forensic units in England. Predictors of future offending included male gender, young age, early onset offending and a diagnosis of personality disorder and all risk instruments demonstrated moderate predictive validity.…”
Section: Introductionmentioning
confidence: 99%